Designing landscape, open space and road entrance based on crime rrevention through environmental design approach : a case study of Taman Kurnia Jaya / Nursahira Mat Nasir - Nursahira, Mat Nasir (2020)
Crime Prevention Through Environmental Design (CPTED) is the one of way to prevent the crime issue from happen by applying the CPTED design Criteria into the residential area. The research aims to designing the landscape, open space and entrance road design criteria in Taman Kurnia Jaya by implement the CPTED approach based on the current situation of design criteria in research study. This area has been choose based on the often happens of crime issues which is house break- ins. In order to reduce the crime rates at the Taman Kurnia Jaya, CPTED is suitable approach that can helps in reducing the level of crime in Taman Kurnia Jaya and focusing on design criteria. The method of this research are using the primary and secondary data. The primary data that has been use in making the research which is online survey using Google Earth 2020 and for secondary data is based on document reviews related with research study. The tools of data collection in research study is using inventory form and base map to relocate the existing design criteria at the study area. This method is gathering information by observation using Google Earth 2020, and supporting the article that published about the case study. Key variable of this study is landscape, open space and entrance road design criteria at site area, the current condition of 3 element are not well designed and not well implement the CPTED principle Taman Kurnia Jaya. There are few place should be improved to prevent the blind spot and hidden space at residential area. from the findings of current site area, there are a few recommendations to improve Taman Kurnia Jaya for more save. It is well designed of structure road, choosing the suitable tree to prevent blocking visibility and hidden space and also well design the open space which is provide variety safe use of open space area. Lastly, the opportunity of this research study are can be earn more knowledge about the CPTED design approach and crime prevention in order to prevent the crime cases to improve the safeness of Taman Kurnia Jaya. The successful recommendations of CPTED implementation will be a meaningful contribution towards the creation of safe residential area that is livable and free from the crime issues therefore helping to improve their quality of life.